Calcilytic Ameliorates Abnormalities of Mutant Calcium‐Sensing Receptor (CaSR) Knock‐In Mice Mimicking Autosomal Dominant Hypocalcemia (ADH). (16th July 2015) - Dong, Bingzi; Endo, Itsuro; Ohnishi, Yukiyo; Kondo, Takeshi; Hasegawa, Tomoka; Amizuka, Norio; Kiyonari, Hiroshi; Shioi, Go; Abe, Masahiro; Fukumoto, Seiji; Matsumoto, Toshio
ABSTRACT Activating mutations of calcium‐sensing receptor (CaSR) cause autosomal dominant hypocalcemia (ADH). ADH patients develop hypocalcemia, hyperphosphatemia, and hypercalciuria, similar to the clinical features of hypoparathyroidism. The current treatment of ADH is similar to the other forms of hypoparathyroidism, using active vitamin D3 or parathyroid hormone (PTH). However, these treatments aggravate hypercalciuria and renal calcification. Thus, new therapeutic strategies for ADH are needed. Calcilytics are allosteric antagonists of CaSR, and may be effective for the treatment of ADH caused by activating mutations of CaSR. In order to examine the effect of calcilytic JTT‐305/MK‐5442 on CaSR harboring activating mutations in the extracellular and transmembrane domains in vitro, we first transfected a mutated CaSR gene into HEK cells. JTT‐305/MK‐5442 suppressed the hypersensitivity to extracellular Ca2+ of HEK cells transfected with the CaSR gene with activating mutations in the extracellular and transmembrane domains. We then selected two activating mutations locating in the extracellular (C129S) and transmembrane (A843E) domains, and generated two strains of CaSR knock‐in mice to build an ADH mouse model. Both mutant mice mimicked almost all the clinical features of human ADH. JTT‐305/MK‐5442 treatment in vivo increased urinary cAMP excretion, improved serum and urinary calcium and phosphate levels by stimulating endogenous PTH secretion, and prevented renal calcification. In contrast, PTH(1‐34) treatment normalized serum calcium and phosphate but could not reduce hypercalciuria or renal calcification. CaSR knock‐in mice exhibited low bone turnover due to the deficiency of PTH, and JTT‐305/MK‐5442 as well as PTH(1‐34) increased bone turnover and bone mineral density (BMD) in these mice. These results demonstrate that calcilytics can reverse almost all the phenotypes of ADH including hypercalciuria and renal calcification, and suggest that calcilytics can become a novel therapeutic agent for ADH. © 2015 American Society for Bone and Mineral Research.